2014
DOI: 10.1136/bcr-2013-203151
|View full text |Cite
|
Sign up to set email alerts
|

Adenomyomatous hyperplasia of the ampulla of Vater presenting as acute pancreatitis

Abstract: We report an interesting and rare case of a man with adenomyomatous hyperplasia of the ampulla of Vater presenting as acute pancreatitis, which to our knowledge, is only the second reported case in the English literature. The patient presented with an acute onset of abdominal pain, nausea and vomiting, without fever, chills or rigours. CT of the abdomen revealed changes of acute pancreatitis with a peripancreatic adenopathy, and abdominal ultrasound revealed a slightly hyperechoic and oedematous head of the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…Endoscopic retrograde cholangiopancreatography (ERCP), another imaging option, is considered the gold standard for the diagnosis of distal CBD abnormalities[15-17]. However, it may induce severe complications such as post-ERCP pancreatitis[18].…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic retrograde cholangiopancreatography (ERCP), another imaging option, is considered the gold standard for the diagnosis of distal CBD abnormalities[15-17]. However, it may induce severe complications such as post-ERCP pancreatitis[18].…”
Section: Discussionmentioning
confidence: 99%
“…3 The first reported case of ampullary adenomyoma was documented by Bravet in 1913. 6,10 The largest case series (describing 13 cases) was reported by Handra-Luca et al in 2003. 3 To date, 58 cases of adenomyoma of the major papilla have been described in the English literature.…”
Section: Discussionmentioning
confidence: 99%
“…3 To date, 58 cases of adenomyoma of the major papilla have been described in the English literature. 3,6,[11][12][13][14][15][16] However, adenomyoma of the minor papilla is extremely rare, with only one case reported. 7 Although a previous review in 1999 showed a higher prevalence in women, with a female/male ratio of 3:1, 17 we did not find any significant difference after reviewing all cases published to date.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the periampullary region, adenomyoma typically presents with biliary obstruction or abdominal pain, with reported cases of acute pancreatitis. 14,22 Lesions in the ileum and jejunum have presented with intussusception and intestinal obstruction, 29 but many reported cases have been incidentally detected. In the small intestine, intussusception is its most common complication, reported in 19 cases.…”
Section: Discussionmentioning
confidence: 99%